ANALISIS TANTANGAN DAN POTENSI PENGEMBANGAN DIGITALISASI DESA - Tobby Putra Kusuma; Asep Nurjaman; Salahudin Salahudin; Sitna Hajar Malawat (AS-SIYASAH : Jurnal Ilmu Sosial Dan Ilmu Politik, 2022)
This study aims to analyze the challenges and potentials in developing village digitization based on potential and hands-on analysis. The research method applied in this study is a qualitative analysis method of challenges and potentials in the development of village digitization. Data analysis using the Nvivo 12 Plus application. The results of the study reveal several potential forms of developing village digitization which are processed into images, namely Central Government Support, Human Resources, Village Programs, Community Participation, and Village Autonomy. Then there are challenges in developing village digitization, namely Regulation, Realization, Participation, Bureaucracy, Culture, and Geographical Location. This village digitization program will provide benefits in optimizing an effective and efficient village government system. In addition, the digitization of villages can increase the potential for improving employee services. This research is expected to contribute to the development of systems, information services, and administrative services in rural areas. In addition, with this research, it is hoped that it can contribute to government policy decisions, especially in village governments in technological developments. So that in the process of developing village digitization, it can realize an open and clean government system. The limitation of this research is that the data used is still limited. The limitation of the research is that the data used is still limited to data obtained from online news and documents from the Ministry of Villages and previous research journals related to the development of village digitization. The next research needs to use primary data, namely direct observation and interviews.